6G in Clinical Applications: Integrating New Network Approaches in Healthcare - Kolb Sven; Jurosch Franziska; Kröger Nicolai; Mehmeti Fidan; Bernhard Lukas; Fuchtmann Jonas; Speidel Stefanie; Kellerer Wolfgang; Wilhelm Dirk (Current Directions in Biomedical Engineering)
The increase in staff shortage, particularly in urgently needed care professions, is becoming an immense problem in the German healthcare system. This critical issue is further intensified by the fact that the healthcare system is still a strongly human-dependent and often insufficiently interconnected environment. Automation, medical robotics and the concept of model-based medicine can play a key role not only in addressing these issues and supporting clinical staff, but also in enabling new applications to improve patient care. While many existing approaches aim to tackle these challenges, they are generally based on current network architectures and standards and are thus constrained by the limitations of these networks. This article highlights the need for a new network approach such as 6G, which offers flexible, dynamic structures, new communication classes and many other new features in order to leverage the true potential of these new technologies.